Kajian Perilaku Konsumen Muslim Terhadap Kampanye Boikot Produk Terafiliasi Israel Berdasarkan Theory of Planned Behavior (TPB): Studi pada Mahasiswa UIN Prof. K. H. Saifuddin Zuhri Purwokerto - Asyifa Nurimani Rahma; Fanda Wulandari; Nur hidayah; Mahardhika Cipta Raharja; Sofia Yustiani Suryandari (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the behavior of Muslim consumers in responding to campaigns to boycott Israeli-affiliated products using the Theory of Planned Behavior (TPB) approach. The research method used is descriptive qualitative with purposive sampling techniques on students at UIN Prof. K.H. Saifuddin Zuhri Purwokerto who understand the boycott issue and are involved in social media discourse related to Palestine. Data were collected through in-depth interviews to explore attitudes, subjective norms, and perceived behavioral control. The results showed that students' positive attitudes toward the boycott were driven by moral values, humanitarian solidarity, and religious beliefs. Subjective norms, especially the influence of family, friends, and social media, reinforced the urge to participate in the boycott. Meanwhile, perceptions of behavioral control vary due to limited information and consumption habit barriers, so that boycott intentions do not always translate into concrete actions. These findings confirm the relevance of TPB in explaining Muslim consumer boycott behavior.